A neural network-based programming paradigm for heat transport of Eyring-Powell fluid with physiological blood flow applications - Abaker A. Hassaballa; Ali Imran; Ines Hilali Jaghdam; Jongsuk Ro (Case Studies in Thermal Engineering)
Complex cilia waves have diverse applications in physiological flow transport across various biological systems. This study presents a novel investigation into the effects of electroosmosis in a non-uniform channel lined with cilia for an Eyring-Powell model fluid. The objective is to examine how fluid transport is influenced in a non-uniform microchannel. Fluid transport characteristics are analyzed within a micro-ciliated channel by applying velocity and thermal slip boundary conditions under the influence of an electric field. Biological fluid flow is modeled using the relevant equations of motion, which are further simplified through low Reynolds number and long wavelength approximations. The physical fluid flow is solved using the bvp5c technique in MATLAB, and the computational scheme's validity is confirmed through artificial neural network (ANN) modeling. Stability analysis is conducted on the bvp5c solution, which is essential for verifying the numerical solution of the boundary value problem. A significant increase in biological fluid transport is observed with the slip parameter, while flow is suppressed by the Helmholtz-Smoluchowski velocity parameter. The temperature of fluid particles increases with the Brinkman number, thermal slip, and electroosmotic parameter but decreases with the thermal conductivity parameter and the Helmholtz-Smoluchowski velocity parameter. Diffusion phenomena are enhanced by the thermal conductivity and Helmholtz-Smoluchowski velocity parameters but are reduced by the concentration slip parameter and electroosmosis. The findings of this investigation may be instrumental in understanding blood transport in small arteries and developing treatments for dysfunctions in such systems.